Verhandelter Netzzugang - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
– In some industries, monopoly is natural. One provider can serve the relevant demand cheaper than two or more firms. If the monopoly is not contestable, i.e. not controlled by a credible threat of entry, regulation is necessary. The essential facilities doctrine is one such regulatory tool. It makes sense, if the following additional conditions are met: upstream or downstream markets are not themselves natural monopolies. The holder of the monopoly is also himself active on one of these markets. The opposite market side is unwilling to buy the components separately. The law can try to safeguard competition on the upstream and downstream markets by giving outside providers a legal right to access the essential facility.Implementing such a legal right is a thorny endeavour, however. Regulatory agencies or the courts must determine a whole, complex long-term relationship. They must regulate price, quality, terms and conditions, implementation, adaptation to changed circumstances, coordination of competing demands of access. Under the conditions of the rule of law, this is highly ambitious. The paper demonstrates, how such an approach could perhaps become effective, nonetheless. And it compares the approach to alternative interventions: replacing the courts by arbitrators; ex ante altering negotiation power; corporatist solutions; structural separation; ex ante in stead of ex post regulation. The corporatist solution has the best performance, but it comes at a high price: rule of law and democratic control are almost completely abolished. Policy makers might in particular prefer to alter ex post legal intervention so that it becomes quicker, more reliable and better informed. This also entails costs in terms of rule of law and democracy, but they are much more modest.
Keywords: K21; K23; L14; K41; L43; L12; D42; L51; L22; L9; 330; Network Industries; essential facility doctrine; natural monopoly; negotiated access; forced arbitration; corporatism; structural separation; Netzregulierung; Verhandlungen; Wettbewerbspolitik; Natürliches Monopol; Deutschland